Prevalence and Associated Factors of Suicidal Behavior Among Patients and Residents in Northwest Ethiopia - Belete, Habte; Misgan, Eyaya; Belete, Tilahun (Frontiers in Psychiatry, 2021)
There are a million suicide deaths in the world annually, 75% of this occur in low- and middle-income countries (LMICs). However, there is a limited resource to prevent suicidal deaths in those regions. The aim was to assess the prevalence of suicidal behavior and associated factors among patients visiting for medical care at Health Center and resident in the community. A comparative study was employed by interviewing, 2625 residents in the community and 1363 patients at health center, for suicidal behavior in northwest Ethiopia, from March 2017 to February 2018. Logistic analysis was employed with adjusted OR (AOR) and 95% Confidence Interval (CI) and with p-value < 0.05. The total prevalence of suicidal behavior (ideation, plan and attempt) was found to be 5.6% (with 95% CI ranges 5% to 6%). It was found to be 4.4% with 95% CI ranges 4% to 5% in the residents while 7.9% with 95% CI ranges 6% to 9% in patients. Female sex, depressive symptoms, physical/verbal abuse and feeling stigmatized were identified as a risk factor of suicidal behavior whereas healthy lifestyle such as eating regular meal of fruits and vegetables, doing physical exercises regularly and having a public health insurance were identified as protective risk factor for suicidal behavior, even after adjusting on being a patient or not. The proportion of suicidal behavior was double in patients than residents. Suicidal behavior should be assessed in patients who visit for medical help and integration of mental health service within the primary health care system is recommended, especially in low-income countries